195k views
0 votes
I need help ASAP
Pls explain your answer ​

I need help ASAP Pls explain your answer ​-example-1

1 Answer

8 votes

Answer:

Explanation:

Start by adding point G, which is the center of the circle, then construct EG, which is the radius of the circle, and CG, which is also the radius of the circle. And by using the Pythagorean theorem on triangle EDG, we have:


(r-2)^2+6^2=r^2

Where r is the radius of the circle.

Then, solve for r:


(r-2)^2+6^2=r^2\\r^2-4r+4+36=r^2\\-4r+40=0\\40=4r\\10=r

And there we have our radius.

I find it surprising that the equation didn't turn into a quadratic.

User Mark Kazakov
by
5.1k points